Etiology of ovine epididymitis in Rio Grande do Sul - Blobel, H.; Fernandes, J. C. T.; Mies Filho, A.; Ramos, A. A.; Trein, E. J. (Pesquisa Agropecuaria Brasileira, 2014)
Brucella-like bacteria were isolated from nine out of 25 rams with epididymitis. Cultured stomach contents of one out of 17 stillborn lambs yielded bacteria that were apparently identical. Epididymitis was produced in all of six experimentally infected rams using five cultures randomly selected from the nine cultures isolated from rams and the bacteria isolated from the stillborn lambs. This was accepted as evidence that the brucella-like bacteria were the cause of ovine epididymitis in Rio Grande do Sul. Histopathologic examination showed inflammatory changes with granulomatous characteristics, however, without specificity.